Tig welding of iron-based shape memory alloys - Martins, Diogo Miguel Parreira (2022)
Shape memory alloys (SMA) are a type of metal alloy with the ability to recover their original dimensions/geometry after undergoing deformation, thus "remembering" their shape. Currently Ni-Ti alloys are the most well-known and commercially used SMA due to their almost perfect shape memory effect (SME) and superelasticity, being used in a variety of applications, from the biomedical to the aerospace industry. Nevertheless, Ni-Ti alloys entail a highly complex and costly manufacturing pro-cess, which hinders their employment in certain industries, where low cost and the simplicity of the process are key characteristics. For these reasons, iron based SMA such as Fe-Mn-Si alloys began to be developed in the 1980s. These alloys exhibit a good degree of SME (although inferior to that observed in Ni-Ti alloys) and are easily machined and formed. Because of their similar composition with conventional steel, Fe-Mn-Si alloys can be produced and processed by the same methods, which greatly decreases their cost, ulti-mately making them more attractive and interesting for applications in the field of civil engineering, for example. It is therefore important to investigate the effects of welding processes on these alloys (espe-cially Tungsten Inert Gas - TIG - welding, being one of the most common in the industry) on micro-structural and mechanical performance, given the inherent nature of the welding process to alter micro-structures and potentially weaken a material mechanically. Within this thesis, the effects of TIG welding on the microstructure of this alloy were studied through optical and electron microscopy and hardness mapping. The mechanical performance between unwelded and welded specimens was compared using uniaxial tensile and cycling tests. The alloy displayed good weldability, with the expected differences in microstructure and a slight deterioration in mechanical performance. As such, these results do not preclude the use of TIG welding on these alloys.